PENINGKATAN KREATIVITAS MELALUI TEKNIK MENGGAMBAR GRAVING PADA ANAK KELOMPOK B DI RA PERMATA IHSAN SOLEAR KABUPATEN TANGERANG - Ulfa Nurbaeti; Atin Fatimah (Jurnal Penelitian dan Pengembangan Pendidikan Anak Usia Dini, 2016)
The purposes of this classroom action research are to know: 1) the implementation of graving draw technique; and 2) the creativity increasement through graving draw technique in Group B RA Permata Ihsan Kabupaten Tangerang. The research was held in August 2015 in RA Permata Ihsan Kabupaten Tangerang. The research subjects are eight 5-6 years old children. Research data were collected through observation, interview, and documentation. Data was analyzed through data reduction, data display, and verification. Based on the data analysis, the 5-6 years old children creativity in RA Permata Ihsan was increased. It can be seen from eight creativity indicators in creativity aspect, such as fluency, flexibility, originality, elaboration, and children patience along the graving draw technique process. The creativity enhancement also can be seen from the creativity percentage. In pre research, the creativity was 30%. It became 53% at cycle 1 and 80% at cycle 2. The creativity percentage at cycle 2 showed that children creativity has reached over the 75% action successful criteria.